2018
DOI: 10.5812/pedinfect.57920
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Synergistic Effect of TiO2, ZnO Nanoparticles and Amphiphilic Peptides (Mastoparan-B, Indolicidin) Against Drug-Resistant Pseudomonas aeruginosa, Klebsiella pneumoniae and Acinetobacter baumannii

Abstract: Backgound: The aims of this study were to evaluate the antimicrobial properties and synergistic effects of nano-titanium dioxide (TiO2), nano-zinc oxide (ZnO) and two synthetic peptides (mastoparan-B, indolicidin) against drug-resistant strains of Pseudomonas aeruginosa, Klebsiella pneumoniae, and Acinetobacter baumannii. Methods: From March to August 2015, a total of 30 (10 each) isolates of the above bacteria were recovered from patients in the ICU of two referral hospitals in Kerman, Iran. The sizes and pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(25 reference statements)
1
10
0
Order By: Relevance
“…These results of this study were accordant with the results of a study done in Babylon by Al-Tameme, (47), which found that the green AgNPs MBC value for P. aeruginosa was (200 μg.mL -1 ), while, Raheem et al, (48) established the MIC of green AgNPs ranged (16-125 μg.mL -1 ) and MBC (125-500 μg.mL -1 ) against E. coli, K. Pneumoniae, S. typhi, S. aureus, P. mirabilis and P. aeruginosa. This result was also agreed with the result of Masoumi and Shakibaie, (49) reported that the values of MIC for AgNPs were between (20-150 µg/ml) that showed high concentration in MIC and MBC values against P. aeruginosa.…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 92%
“…These results of this study were accordant with the results of a study done in Babylon by Al-Tameme, (47), which found that the green AgNPs MBC value for P. aeruginosa was (200 μg.mL -1 ), while, Raheem et al, (48) established the MIC of green AgNPs ranged (16-125 μg.mL -1 ) and MBC (125-500 μg.mL -1 ) against E. coli, K. Pneumoniae, S. typhi, S. aureus, P. mirabilis and P. aeruginosa. This result was also agreed with the result of Masoumi and Shakibaie, (49) reported that the values of MIC for AgNPs were between (20-150 µg/ml) that showed high concentration in MIC and MBC values against P. aeruginosa.…”
Section: X-ray Diffraction (Xrd)supporting
confidence: 92%
“…As previously described, a checkerboard titration method was used on standard 96-well microtitre plates to determine the fractional inhibitory concentration indexes (FICI) of each antibacterial compound. The degree of antimicrobial synergy is frequently expressed in terms of FIC 27 , 28 . FIC is calculated by dividing the MIC for a drug in combination by the MIC for drugs acting alone.…”
Section: Methodsmentioning
confidence: 99%
“…This combination showed additive effects against A. baumannii and K. pneumoniae . The combination of nanoparticles (TiO 2 NPs and ZnO NPs) had an additive effect on A. baumannii and K. pneumoniae strains [ 146 ]. Recently, Hérault et al tested the antibacterial effect of silver-containing titanium dioxide nanocapsules against E. coli , S. aureus , and MDR S. aureus .…”
Section: New Therapeutic Strategies: Combinatorial Treatmentsmentioning
confidence: 99%